Palliative dental care for patients with late-stage hemato-oncology disease - Ali Alqarni; Hassan Abed; Amal Ashour; Haytham Tayeb; Ahmed Alghamdi; Hussam Abualola (Wolters Kluwer Medknow Publications, 2023)
Patients with hematological malignancies are at increased risk of oral complications such as dental pain, oral mucositis, discomfort, oral candidiasis, and infection. Some hemato-oncology patients feel acute dental pain during the active stage of cancer therapy, which necessitates relieving dental pain in addition to other palliate dental care, specifically, if the patient is on end-of-life care. The goal of palliative dental care is to eliminate any source of dental pain, which helps to improve a patient's quality of life. We report a case of a 78-year-old woman who was diagnosed with myelodysplastic syndrome (MDS) at the late stage of cancer and was referred to improve her esthetic and eating function during the active phase of chemotherapy. The aim of this case report was to describe palliative dental care for patients who require end-of-life care at the late stage of cancer and to discuss the dental management of patients with MDSs.